1998
DOI: 10.1063/1.476685
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio study for the low-lying electronic states of Al3 and Al3−: The photoelectron spectroscopy of Al3−

Abstract: The low-lying electronic states of Al3 (2A1,2B1,4A2,4B1,2B2,2A1,4B2,6A2) and Al3− (1A1,3B2,3A1,3A2,3B1,5A2) are studied by coupled-cluster methods with a [6s5p2d1f] basis set. The geometries and harmonic frequencies are calculated by the coupled-cluster single double triple (CCSD(T)) correlation method with frozen core and virtual molecular orbitals. The energetic splittings at CCSD(T) geometries are calculated also by the CCSDT method. The calculated vibrational frequencies of the observed states of Al3 (A12,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
20
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 35 publications
11
20
0
Order By: Relevance
“…Subsequent computational studies suggested that the 2.57 eV feature is due to a transition ͑X1͒ from the Al 3 − ground state to this 2 B 2 state. 5 According to the present calculations ͑Table I͒, the adiabatic electron detachment energy for this transition is 2.654 eV ͑CC͒, in agreement with the observed value. In addition, the two-electron nature of this transition would be consistent with the relatively weak observed intensity of the 2.57 eV band.…”
Section: Iiib7 Uv Photodetachment Transitionssupporting
confidence: 91%
See 2 more Smart Citations
“…Subsequent computational studies suggested that the 2.57 eV feature is due to a transition ͑X1͒ from the Al 3 − ground state to this 2 B 2 state. 5 According to the present calculations ͑Table I͒, the adiabatic electron detachment energy for this transition is 2.654 eV ͑CC͒, in agreement with the observed value. In addition, the two-electron nature of this transition would be consistent with the relatively weak observed intensity of the 2.57 eV band.…”
Section: Iiib7 Uv Photodetachment Transitionssupporting
confidence: 91%
“…For the 4.3 eV band B, 36 reported as C at 4.4 eV in the earlier UV study, 37 an alternative assignment has been suggested based on equation-of-motion CC calculations at the Al 3 ground state geometry. 5 This transition ͑X2͒ is to a 2 A 1 Ј͑ 2 A 1 ͒ ͑͑1a 2 Љ͒ 0 ͑2a 1 Ј͒ 2 ͑3a 1 Ј͒ 1 ͒ state with a calculated energy of 2.45 eV above the Al 3 ground state, giving a predicted photodetachment energy of 4.39 eV. 5 This 2 A 1 Ј͑ 2 A 1 ͒ state, which would require a two-electron process to be accessed from the Al 3 − ground state, was not identified in the present PBE0 or time dependent PBE0 calculations.…”
Section: Iiib7 Uv Photodetachment Transitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…1, all possible AlB À 2 geometries such as C 2v and C 1v isomers are optimized as the stable structures. The calculated results illustrate that the isosceles triangle 2a isomer with the symmetry of C 2v and electronic state of 1 A 1 is the lowest-energy structure, which can be regarded as two substitutions of Al atoms by B atoms in a triangle Al À 3 anion [17,20,21] and can also be viewed as a substitution of a B atom by an Al atom in the equilateral triangle B À 3 cluster [12]. The energetically closest isomer 2b is a triplet state with C 1v symmetry, which is consistent with that offered in Ref.…”
Section: Geometries and Growth Pattern Behaviorsmentioning
confidence: 99%
“…These studies have confirmed the planar or quasi-planar structures are more stable than any three-dimensional structures for an extended size range at least up to n = 23. While for the aluminum atom belonging to the same group with that of the boron atom in the periodic table, the structure transition of the Al n clusters from planar to three-dimensional (3D) occurs at n = 5 [16][17][18][19][20][21][22][23][24]. The substitution of boron clusters by aluminum atoms provides unique chemical environment, which may induce a significant change of the electronic properties and the possibility of new types of materials.…”
Section: Introductionmentioning
confidence: 99%